Neurotransmitter Modulation of Carotid Body Germinal Niche - Sobrino, Verónica; Platero-Luengo, Aida; Annese, Valentina; Navarro-Guerrero, Elena; González-Rodríguez, Patricia; López-Barneo, José; Pardal, Ricardo (International journal of molecular sciences, 2020)
The carotid body (CB), a neural-crest-derived organ and the main arterial chemoreceptor in mammals, is composed of clusters of cells called glomeruli. Each glomerulus contains neuron-like, O2-sensing glomus cells, which are innervated by sensory fibers of the petrosal ganglion and are located in close contact with a dense network of fenestrated capillaries. In response to hypoxia, glomus cells release transmitters to activate afferent fibers impinging on the respiratory and autonomic centers to induce hyperventilation and sympathetic activation. Glomus cells are embraced by interdigitating processes of sustentacular, glia-like, type II cells. The CB has an extraordinary structural plasticity, unusual for a neural tissue, as it can grow several folds its size in subjects exposed to sustained hypoxia (as for example in high altitude dwellers or in patients with cardiopulmonary diseases). CB growth in hypoxia is mainly due to the generation of new glomeruli and blood vessels. In recent years it has been shown that the adult CB contains a collection of quiescent multipotent stem cells, as well as immature progenitors committed to the neurogenic or the angiogenic lineages. Herein, we review the main properties of the different cell types in the CB germinal niche. We also summarize experimental data suggesting that O2-sensitive glomus cells are the master regulators of CB plasticity. Upon exposure to hypoxia, neurotransmitters and neuromodulators released by glomus cells act as paracrine signals that induce proliferation and differentiation of multipotent stem cells and progenitors, thus causing CB hypertrophy and an increased sensory output. Pharmacological modulation of glomus cell activity might constitute a useful clinical tool to fight pathologies associated with exaggerated sympathetic outflow due to CB overactivation.